In-depth Study of Canonical Hadith Books - Samsudin; Engkos Kosasih; Muhammad Al Mighwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The study of canonical hadith books is an important field of research in Islamic studies, which is related to the existence, authority, and interpretation of hadith that is considered valid in the Islamic tradition. This research aims to provide an in-depth understanding of canonical hadith by analyzing various aspects, from its historical validity to its relevance in contemporary contexts.The research methods used include textual, historical, and contextual analysis of hadiths that are recognized canonically in primary and secondary sources. In addition, a critical approach to these sources is also applied to understand the process of collection, redaction, and transmission of canonical hadith.The results of this study reveal the complexity and diversity of canonical hadith, as well as its impact on the understanding and practice of Islam. In addition, this study also discusses the relevance of canonical hadith in contemporary social, political, and religious contexts, as well as the interpretive challenges faced by Muslim scholars.An in-depth study of the canonical hadith book has significant implications in deepening the understanding of the Islamic intellectual heritage, as well as broadening the insight into interpretive dynamics in the Islamic scientific tradition.